Islamization and Javanese Culture in the Era of Sultan Agung: The Dynamics of Education, Art and Spirituality in the Mataram Sultanate - Azna, Tiwi Fadlilatul; Dhiyaulhaq, Nafila Firda (INDONESIAN JOURNAL OF SUSTAINABILITY, 2026)
This article affirms the concept of productive syncretism as the main analytical framework for understanding the Islamization of Javanese culture during the reign of Sultan Agung. Islamization is not positioned as a process of cultural homogenization, but rather as a creative mechanism that brings together universal Islamic values with local Javanese traditions in a dialogical and functional manner. Through a qualitative historical-cultural approach, analysis of texts such as Serat Sastra Gending and the views of Javanese cultural experts show that this syncretism gave rise to new forms of praxis in palace education, religious artistic expression, and Sufi-influenced spirituality. The research findings show that productive syncretism allows Islamic values to not only be accepted but also reinterpreted in accordance with Javanese cosmology, resulting in a sustainable and contextual cultural system. Thus, the main contribution of this study lies in offering the conceptual framework of productive syncretism as a lens for reading the Islamization of the archipelago, which is relevant for strengthening character, moderate religious diversity, and the preservation of Javanese-Islamic culture in a contemporary context.Keywords: Islamization of Javanese culture, Sultan Agung, Islamic education, religious art, spirituality.